The Role of Islamic Religious Education Teachers in Improving the Ability to Read the Qur'an through the Al Wafa Method - Wahyuni Ahadiyah, Hanifah Eliyansah; Wahyuni Ahadiyah, Hanifah Eliyansah (EDUCATIO : Journal of Education, 2025)
This research is motivated by the low ability of students to read the Qur’an at SMP Negeri 5 Lamongan, where many students are still unable to recognize hijaiyah letters or read the Qur’an properly according to tajweed rules. Therefore, the active role of Islamic Religious Education teachers and the implementation of appropriate learning methods are urgently needed to improve students’ Qur’anic reading skills. This study aims to describe the role of Islamic Religious Education teachers in improving students’ Qur’anic reading skills through the Al Wafa method at SMP Negeri 5 Lamongan, as well as to identify the supporting and inhibiting factors in its implementation. This research uses a descriptive qualitative approach with data collected through observation, interviews, and documentation. The results show that teachers play a vital role as educators, instructors, mentors, facilitators, and role models in Qur’anic education. The Al Wafa method is considered effective due to its enjoyable, illustrated, and easily understood approach, which enhances students' ability to read the Qur’an. Supporting factors include teacher enthusiasm, the availability of learning materials such as the Al Wafa book, and student motivation. Meanwhile, obstacles include limited instructional time, lack of parental support, and a shortage of teaching staff. Therefore, consistent application of the Al Wafa method significantly improves students' Qur’anic reading skills.